A Study on Cloud Platform for Multiple IoT Nodes with Enviormental Sensor - Nazri, Muhammad Aidil; Saparudin, Faiz Asraf (Progress in Engineering Application and Technology, 2023)
A new and rapidly expanding concept, the "Internet of Things" (IOT), has developed in recent years. To recover from the current financial and economic instability, the global economy has to establish new economic development growth spots. The Internet of Things (IoT) might greatly increase economic benefits and reduce costs. As a result, all related industries are growing at a breakneck pace. Multiple industries, including cloud server and IoT module manufacturing, are competing to provide the most effective system, device, and platform to back R&D and meet market demand. Because of this, IoT businesses are vying to prove themselves as the most trustworthy and capable in order to attract customers and generate revenue. Users at varying levels of expertise also need their own independent, trustworthy system. The goals are to design a cloud platform for multiple IoT nodes with environmental sensor are relevant to be apply on simple or even complex task based on demand of the usage. The system that been design are created having a reliable data communication within the system and were constructed with effective workflow.